SUATU PERBANDINGAN PENGATURAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DI TAIWAN DAN DI INDONESIA - Yunari, Sri Bakti (Legality : Jurnal Ilmiah Hukum, 2016)
Regulation comparison between Corporate Social and Environmental Responsibility (CSER) in Indonesia and Corporate Social Responsibility in Taiwan, aiming to compare the regulation of CSR in Taiwan and CSER in Indonesia. This Comparison carried out using the normative research method, which analyzed descriptively illustrating that regulation CSER at Art 74 Indonesian Law No. 40 of 2007 on Limited Company in conjuction with Government regulation Number 47 of 2012 on Social and Environmental Responsibility of limited company compared with Corporate Social Responsibility Regulation in Taiwan as required by the Taiwan Stock Exchange Corporation (TWSE) and GreTai Securities Market (GTSM)